2020
DOI: 10.3390/educsci10030057
|View full text |Cite
|
Sign up to set email alerts
|

Read Like Me: An Intervention for Struggling Readers

Abstract: The current study reports on a reading intervention method titled Read Like Me. The intervention utilizes a stacked approach of research-based methods, including reading aloud, assisted reading, and repeated reading. The student involved was a second-grade boy reading below grade level who was identified as dyslexic and diagnosed with attention deficit hyperactive disorder. Using a single-case experimental design, the intervention was monitored in four phases, including a baseline, intervention coupled with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Recent studies have begun to measure the influence of SPORT on tutee prosody, extending the theme first described by Flood et al (2005). However, to date, only four studies investigating oral reading prosody have been conducted (Brown et al, 2018; Young et al, 2015; Young et al, 2020; Young, Pearce, et al, 2018). These preliminary results demonstrate positive outcomes in prosody for tutees who read aloud synchronously with partners.…”
Section: History and Evolution Of Sport Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have begun to measure the influence of SPORT on tutee prosody, extending the theme first described by Flood et al (2005). However, to date, only four studies investigating oral reading prosody have been conducted (Brown et al, 2018; Young et al, 2015; Young et al, 2020; Young, Pearce, et al, 2018). These preliminary results demonstrate positive outcomes in prosody for tutees who read aloud synchronously with partners.…”
Section: History and Evolution Of Sport Methodsmentioning
confidence: 99%
“…Two studies calculated effect sizes for tutee prosody gains, each reporting large effects ( d = 1.44, Young et al, 2015; d = 1.03, Young, Pearce, et al, 2018). Further, raw score gains appear positive for tutees on the 16‐point scale in the MFDS (4.4, Brown et al, 2018; 2.79; Young et al, 2015; 2.8, Young, Pearce, et al, 2018; 4.16, Young, Pearce, et al, 2018; 5, Young et al, 2020). Again, these outcomes may be influenced by tutee grade level; the study with the smallest reported gains (Young et al, 2015) was composed primarily of Grade 4 and 5 students, whereas the other three studies used Grade 2 and Grade 3 students.…”
Section: Synthesis Of Tutee Academic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there are a lot of researches done on the positive effect of incorporating technology in learning. However, as stated by Young, Lagrone and McCauley (2020), "reading research has been conducted for centuries, but yet, there is still a need for additional reading interventions, as no one intervention will work for every student" (p. 3). Considering the interest of the students and the approachability of this tool to be carried out with their parents at home, video recording of reading session project was introduced to motivate students to read more.…”
Section: Motivating Struggling Malaysian Primary Esl Readers Through the 'Read And Record Project'mentioning
confidence: 99%
“…The reading literacy ability of elementary school students from the start will be a big asset for the development of interest and reading habits. Interests and reading habits can lead to the ideals of the nation (Young et al, 2020). The habit of reading is the key for a nation to progress, to become a culture by being taught and having a disciplinary process.…”
mentioning
confidence: 99%